Pengelolaan Peserta Didik Di Masa Pandemi (Studi Kasus Di Raudhatul Athfal Humaira’ Provinsi Bengkulu) - Nur Ifani, Nadia; Connie (UNIVERSITAS BENGKULU, 2023)
The purpose of this study was to describe the process of student management at Raudhatul Athfal Humaira’ Bengkulu city during pandemic. This research is a qualitative descriptive study. The research subjects were the Headmaster, teachers,and student’s parents. Data collection techniques using interviews, observations, and documentation. The results showed that student management process at Raudhatul Athfal Humaira' can operate in accordance with government guidelines. Although there are still numerous flaws and problems that are out of our control in reality. Human resource development and comprehensive teacher preparation, including pedagogical, professional, personality, and social competencies, must continue to be prioritized. Particularly instructional and professional in nature. So that teachers are always prepared for changing situations and changes in the field of education.Solutions made by schools increase teacher knowledge through training and teacher group discussion forums.